Acupuncture for acute musculoskeletal pain management in the emergency department and continuity clinic: a protocol for an adaptive pragmatic randomised controlled trial. Issue 9 (23rd September 2022) - Eucker, Stephanie A; Glass, Oliver; Staton, Catherine A; Knisely, Mitchell R; O'Regan, Amy; De Larco, Christi; Mill, Michelle; Dixon, Austin; TumSuden, Olivia; Walker, Erica; Dalton, Juliet C; Limkakeng, Alexander; et al.
Abstract : Introduction: Chronic musculoskeletal pain causes a significant burden on health and quality of life and may result from inadequate treatment of acute musculoskeletal pain. The emergency department (ED) represents a novel setting in which to test non-pharmacological interventions early in the pain trajectory to prevent the transition from acute to chronic pain. Acupuncture is increasingly recognised as a safe, affordable and effective treatment for pain and anxiety in the clinic setting, but it has yet to be established as a primary treatment option in the ED. Methods and analysis: This pragmatic clinical trial uses a two-stage adaptive randomised design to determine the feasibility, acceptability and effectiveness of acupuncture initiated in the ED and continued in outpatient clinic for treating acute musculoskeletal pain. The objective of the first (treatment selection) stage is to determine the more effective style of ED-based acupuncture, auricular acupuncture or peripheral acupuncture, as compared with no acupuncture. All arms will receive usual care at the discretion of the ED provider blinded to treatment arm. The objective of the second (effectiveness confirmation) stage is to confirm the impact of the selected acupuncture arm on pain reduction. An interim analysis is planned at the end of stage 1 based on probability of being the best treatment, after which adaptations will be considered including dropping the less effective arm, sample size re-estimation and unequal treatment allocation ratio (eg, 1:2) for stage 2. Acupuncture treatments will be delivered by licensed acupuncturists in the ED and twice weekly for 1 month afterward in an outpatient clinic. Ethics and dissemination: This study has been reviewed and approved by the Duke University Health System Institutional Review Board. Informed consent will be obtained from all participants. Results will be disseminated through peer-review publications and public and conference presentations. Trial registration number: NCT04290741 .